Major diseases manifesting by vestibular vertigo: Treatment and rehabilitation - V. A. Parfenov; L. M. Antonenko (Неврология, нейропсихиатрия, психосоматика, 2015)
Betahistine hydrochloride is the drug of choice for the treatment of vestibular vertigo in the presence of benign paroxysmal positional vertigo, Meniere's disease, and vestibular neuronitis. Effective combination therapy regimens that contain, along with drugs from other pharmacological groups, betahistine hydrochloride that improves blood circulation in the vestibular structures, accelerates vestibular compensation, and prevents recurrent dizzy spells, have been elaborated to treat central vestibular vertigo in migraine-associated dizziness and in acute cerebrovascular accident. Of great importance is a combination of drug therapy and the current rehabilitation methods for vestibular diseases, which contribute to prompter and complete recovery of vestibular function. Biofeedback instrumental rehabilitation techniques using a stabilographic platformare highly effective. Successful treatment depends on the correctness of the established diagnosis. The diagnosis of peripheral and central vestibular vertigo frequently poses challenges. The essential reason for this is physicians’ unawareness about outpatient methods for the diagnosis of major vestibular diseases when the patient is at a doctor. It is important to follow a vestibular system study protocol since the use and correct assessment of diagnostic tests in most cases make it possible to estimate the degree of vestibular analyzer injury and to make an accurate diagnosis. The paper describes the diseases that are the most common causes of vestibular vertigo. The most effective methods for their treatment and current rehabilitation methods are discussed.